Odyssey Self Reflection - Oversized clothes / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
My idea was inspired from my own confidence in donning plus-size outfits. My artwork explained my point of view of the different sizes of clothes. The elements and principles in the artworks were based on texture, space form, balance of the form, contrast as well as value of the artworks.